Pengaruh Persepsi Kualitas, Persepsi Kesesuaian, Persepsi Kesulitan Pada Sikap Konsumen Terhadap Brand Extention - Elida Ningtyas Herlina; Siti Khoiriyah (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2010)
The aim of this research is to examine the influence of the perceived quality, perceived fits, and perceived difficulty to attitude toward brand extension. Using purposive sampling method, 150 readers of a local newspaper and listeners of a news radio at Surakarta were collected as respondents. Four hypotheses were tested using moderated regression analysis. The results indicated that attitude toward brand extension were affected by perceived fit (dimensions of transfer), perceived difficulty, interaction between perceived qualityperceived fit (dimension of substitute) and interaction between perceived quality-perceived fit (dimension of complement). Perceived quality has not significant effect to attitude toward brand extension